Handbook of mental health and aging - Hantke, Nathan; Etkin, Amit; O'Hara, Ruth (San Diego,United States: Academic Press is an Imprint of Elsevier, 2020)
'Handbook of Mental Health and Aging, Third Edition, contains state-of-the-art research in the biological, behavioral and social sciences, presenting the cutting-edge in current practice in psychiatry, neurology, social work, nursing, psychology and pharmacology. New expert lead editors bring fresh life and a new focus to this classic reference'--
Keywords: Older people -- Mental health; Older people -- Psychology; Aging; Mental Disorders; Geriatric psychiatry